Quality by design enabled formulation development of regorafenib monohydrate loaded PEGylated PLGA polymeric nanoparticles: Enhanced oral bioavailability and biopharmaceutical attributes - Dhananjay Panigrahi; Suryakanta Swain; Pratap Sahu; Debashish Ghose; Bikash Ranjan Jena (Nanomedicine Journal, 2024)
Objective(s): Using a quality-by-design methodology, the current research is aimed to prepare and enhance the PEGylated PLGA-loaded regorafenib monohydrate polymeric nanoparticles for enhancing oral bioavailability and biopharmaceutical attributes. The oral multi-kinase inhibitor inhibits VEGFR2-TIE2 tyrosine kinases on two separate targets, which results in anti-angiogenic activity. It also inhibits stromal and oncogenic receptor tyrosine kinases. Materials and Methods: The current study developed nanosized, biocompatible, and PEGylated PLGA polymeric nanoparticles to administer regorafenib monohydrate to patients with metastatic colon cancer. This was accomplished using a modified nanoprecipitation technique to make drug-encapsulated PEGylated PLGA nanoparticles with poloxamer 188 as a stabilizer. Results: The polymeric nanoformulations were characterized for zeta potential, distribution of particle size, entrapment efficiency, DSC, FT-IR, X-RD, and SEM. Both in vitro and in vivo experimental studies were performed for the pure drug and the improved nanoparticle formulation.Conclusion: The nanoparticles obtained from optimization studies  were found to have smaller particle sizes, higher entrapment efficiency (%), drug loading capacity, spherical shape particles, amorphous drug embedded matrix, and a biphasic delayed release pattern. These findings suggest that drug-loaded PEGylated PLGA nanoparticles are a potent formulation for the treatment of colon cancer, with improved oral bioavailability and biopharmaceutical properties.